1999
DOI: 10.1902/jop.1999.70.6.604
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Modulate Interleukin‐6 Production by Gingival Fibroblasts In Vitro

Abstract: We concluded that elevated levels of androgens, specifically testosterone and dihydrotestosterone, could affect the stromal cell response to an inflammatory challenge by downregulation of IL-6 production. This in vitro study lends support to the hypothesis that increased hormones during pregnancy or puberty could modulate the development of localized inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 42 publications
5
53
0
7
Order By: Relevance
“…Whereas both testosterone and DHT provoked a significant increase in macrophage IL-6 gene expression without greatly affecting TNF-␣ or TGF-␤1 mRNA levels, fibroblast IL-6 and TGF-␤1 mRNA levels and protein secretion were significantly reduced by treatment with testosterone or DHT and TNF-␣ mRNA expression decreased in response to exposure to DHT. These findings are partially corroborated by previous studies which demonstrated that DHT and testosterone inhibit IL-6 production by oral and gingival fibroblasts and that DHT but not testosterone stimulates secretion of IL-6 by Kupffer cells (Coletta et al, 2002;Gornstein et al, 1999;Parkar et al, 1998;Schneider et al, 2003). The failure of testosterone to enhance macrophage TNF-␣ gene expression contrasts sharply with the situation in mice, in which testosterone has been shown to increase both basal and LPS-induced mRNA levels (Ashcroft and Mills, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…Whereas both testosterone and DHT provoked a significant increase in macrophage IL-6 gene expression without greatly affecting TNF-␣ or TGF-␤1 mRNA levels, fibroblast IL-6 and TGF-␤1 mRNA levels and protein secretion were significantly reduced by treatment with testosterone or DHT and TNF-␣ mRNA expression decreased in response to exposure to DHT. These findings are partially corroborated by previous studies which demonstrated that DHT and testosterone inhibit IL-6 production by oral and gingival fibroblasts and that DHT but not testosterone stimulates secretion of IL-6 by Kupffer cells (Coletta et al, 2002;Gornstein et al, 1999;Parkar et al, 1998;Schneider et al, 2003). The failure of testosterone to enhance macrophage TNF-␣ gene expression contrasts sharply with the situation in mice, in which testosterone has been shown to increase both basal and LPS-induced mRNA levels (Ashcroft and Mills, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…The mechanism by which testosterone effects these responses is uncertain, but laboratory evidence has suggested that testosterone suppresses proinflammatory cytokines and may up-regulate antiinflammatory cytokines. Despite the varied approach of these studies, the response to testosterone appears to be similar, so that testosterone incubated in cell culture attenuates the production of inflammatory cytokines such as TNF␣, IL-1␤, and IL-6 in human macrophages (8), human monocytes (9), human gingival fibroblasts (10), murine and human osteoblasts (11,12), and human endothelial cells (13). Furthermore, antiinflammatory cytokines such as IL-10 are stimulated in the presence of testosterone (14,15).…”
mentioning
confidence: 99%
“…Diversos estudos publicados na literatura sugeriram que o aumento da inflamação gengival influenciada pelo aumento dos níveis dos hormônios sexuais, como aquele observado durante as fases de puberdade e gestação, não estão associadas com aumento no índice de placa (Kalkwarf, 1978;Pankhurst, Waite et al, 1981;Sooriyamoorthy e Gower, 1989;Amar e Chung, 1994;Machtei, Mahler et al, 2004) (Kalkwarf, 1978;Kornman e Loesche, 1982;Amar e Chung, 1994;RaberDurlacher, Van Steenbergen et al, 1994;Gornstein, Lapp et al, 1999;Reinhardt, Payne et al, 1999;Machtei, Mahler et al, 2004). Porém, essa associação não foi observada em outros estudos (Knight e Wade, 1974;Jensen, Liljemark et al, 1981;Preshaw, Knutsen et al, 2001).…”
Section: Discussionunclassified
“…Além disso, a alteração hormonal observada durante a gravidez influencia a proliferação de algumas espécies bacterianas, especialmente Prevotella intermedia (Kornman e Loesche, 1980;1982;Sooriyamoorthy e Gower, 1989;Muramatsu e Takaesu, 1994;Raber-Durlacher, Van Steenbergen et al, 1994) e Campylobacter rectus (Yokoyama, Hinode et al, 2005). Por outro lado, os hormônios sexuais também estimulam a vasodilatação e permeabilidade vascular (Lindhe e Branemark, 1967b;a;Hugoson, 1970;Mohamed, Waterhouse et al, 1974;Brooks, 1980;Gornstein, Lapp et al, 1999), aumentam a síntese de mediadores inflamatórios (Goodson, Dewhirst et al, 1974;Elattar, 1976;Machtei, Mahler et al, 2004;Lapp e Lapp, 2005), a quimiotaxia de neutrófilos (Miyagi, Aoyama et al, 1992;Ferris, 1993) e diminuem a quantidade de células T e B no tecido conjuntivo gengival (O'neil, 1979a;Aboul-Dahab, ElSherbiny et al, 1994).…”
Section: Discussionunclassified
See 1 more Smart Citation